Antimicrobial and antioxidant surface modification toward a new silk-fibroin (SF)-l-Cysteine material for skin disease management - Nogueira, Frederico (2016)
A novel dressing material – silk fibroin fabric (SF)-l-Cysteine (l-Cys) – is here developed to be used asstandard treatment for atopic dermatitis (AD), which combines comfort, thermic, and tensile strengthproperties of silk materials with antioxidant and antimicrobial effects of l-Cys. A careful understand-ing about the linking strategies is needed in order not to compromise the bioavailability of l-Cys anddeplenish its bioactivity. Durability was also addressed through washing cycles and compared with hos-pital requirements, according to international Standard EN ISO 105-C06:2010. The present research alsoanalyze the interactions between Staphylococcus aureus and SF-l-Cys under simulating conditions of ADand demonstrated the effectiveness of a double covalent grafting, with the importance of SF tyrosine(Tyr) covalent linkage with l-Cys (SF-g-l-Cys/Tyr-g-l-Cys) even after several washing cycles, twenty five,whereas for a disposable application a single covalent mechanism of grafting l-Cys proved to be suffi-cient (SF-g-l-Cys). Results showed effective antimicrobial activities exhibiting higher inhibition ratios of98.65% for SF-g-l-Cys after 5 washing cycles, whereas 97.55% for SF-g-l-Cys/Tyr-g-l-Cys after 25 washingcycles, both at pH 9.5 grafting strategy. Furthermore, it is also reported a non-protumoral effect of l-Cys. Anew advance is herein achieved at the world of medical antimicrobial textiles tailored to address woundmoisture environment and exudate self-cleaning, which may open novel applications as complementarytherapy for AD disease.